Arthroscopic treatment of deep gluteal syndrome and the application value of high-frequency ultrasound - Guanjun Sun; Weili Fu; Qingshan Li; Yi Yin (BMC Musculoskeletal Disorders, 2023)
Abstract Purpose This study aimed to evaluate the efficacy of arthroscopic sciatic neurolysis for treating deep gluteal syndrome (DGS) and to analyse the application value of high-frequency ultrasound during perioperative period. Methods Between June 2020 and February 2022, 30 patients with DGS who underwent failed conservative treatment were retrospectively analysed. Lateral arthroscopic exploration of the deep gluteal space and sciatic neurolysis were performed. In addition to pelvic X-ray, lumbar disc and hip magnetic resonance imaging (MRI), ultrasonography of the sciatic nerve was also performed in all patients. The visual analogue scale pain score (VAS), modified Harris hip score (mHHS) and Benson symptom-rating scale were used to evaluate the clinical efficacy. The correlation between preoperative sciatic nerve ultrasound and arthroscopic findings was analysed. Results The median follow-up for these patients was 13 months (range,12–21 months). Preoperative ultrasonography showed precise morphological changes in 26 sciatic nerves of patients. The VAS score decreased from 5.0 (4.0, 6.0) preoperatively to 0.5 (0, 1.0) postoperatively (p < 0.001), and the mHHS increased from 64.0 (57.0, 67.0) preoperatively to 95.0 (93.0, 97.0) postoperatively (p < 0.001). The Benson symptom score was excellent in 15 cases, good in 12 cases, fair in 2 cases, poor in 1 case; thus, the score was excellent or good in 90% of the cases. Preoperative ultrasound diagnosis and intra-operative findings matched up in all cases. There were four cases of transient numbness in the posterior thigh. Conclusions Arthroscopic sciatic neurolysis is a safe and effective treatment option for DGS patients who fail conservative treatment. Ultrasound diagnosis matched the arthroscopic findings perfectly. Preoperative Doppler ultrasound can assist surgical decision-making, guide intraoperative release.